2021
DOI: 10.1016/j.ajic.2020.06.212
|View full text |Cite
|
Sign up to set email alerts
|

Drape to prevent disease transmission during endotracheal intubation

Abstract: Endotracheal intubation poses high risk of transmission of severe acute respiratory syndrome coronavirus 2 and other respiratory pathogens. We designed and here describe a protective drape that we believe will greatly reduce this risk. Unlike the intubation box that has been described prior, it is portable, disposable, and does not restrict operator dexterity. We have used it extensively and successfully during the height of the corona virus disease of 2019 outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The plans for this structure were quickly shared on social media [13], and Canneli et al were the first to report on its use in the scientific literature [14]. Subsequently, after this idea was promoted by news and social media and the device was proliferated and distributed to some users, multiple variations of barrier devices were introduced [15][16][17][18][19][20][21]. These barriers were applied not just for endotracheal intubation and airway management (Figure 2B,C) but were utilized in various aspects of medical care, as well as applied to facilitate other forms of human interaction during the pandemic (Figure 3).…”
Section: The Development Of Barrier Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plans for this structure were quickly shared on social media [13], and Canneli et al were the first to report on its use in the scientific literature [14]. Subsequently, after this idea was promoted by news and social media and the device was proliferated and distributed to some users, multiple variations of barrier devices were introduced [15][16][17][18][19][20][21]. These barriers were applied not just for endotracheal intubation and airway management (Figure 2B,C) but were utilized in various aspects of medical care, as well as applied to facilitate other forms of human interaction during the pandemic (Figure 3).…”
Section: The Development Of Barrier Systemsmentioning
confidence: 99%
“…In addition, the visualization of the indirect monitor may be difficult if the screen is mounted on the videoscope itself [42]. Subsequently, plastic sheets were modified by making openings in the plastic sheet, allowing for the airway device and ETT to be passed from above the sheet or for the provider's hands to reach through [17,20] (Figures 9 and 11). Even if the monitor was affixed to the videoscope, the operator would still have an unobstructed view if the screen remained above the barrier.…”
Section: Combining Barrier Systems With the Video Intubating Styletdmentioning
confidence: 99%
“…FFP2 were worn as standard masks in 83.2% of ICUs. 81.0% used additional isolation measures such as videolaryngoscopy and intubation drape frames [ 30 ]. At the time of the survey, a full-body suit was worn in only 9.5% of the units.…”
Section: Resultsmentioning
confidence: 99%
“…Although several variations of aerosol boxes and transparent plastic drapes have been built recently, it is uncertain how often they have been used in clinical settings [4,9,16]. In addition, it is uncertain if they extend intubation time.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that droplet spread decreased with the use of an aerosol box [4]. Furthermore, a transparent plastic drape was also designed to decrease the spread of droplets during endotracheal intubation [9,20].…”
Section: Introductionmentioning
confidence: 99%